Endovascular revascularisation versus conservative management for intermittent claudication - Fakhry, Farzin (Cochrane Database Syst Rev, 2018)
BACKGROUND: Intermittent claudication (IC) is the classic symptomatic form of peripheral arterial disease affecting an estimated 4.5% of the general population aged 40 years and older. Patients with IC experience limitations in their ambulatory function resulting in functional disability and impaired quality of life (QoL). Endovascular revascularisation has been proposed as an effective treatment for patients with IC and is increasingly performed. OBJECTIVES: The main objective of this systematic review is to summarise the (added) effects of endovascular revascularisation on functional performance and QoL in the management of IC. SEARCH METHODS: For this review the Cochrane Vascular Information Specialist (CIS) searched the Specialised Register (February 2017) and the Cochrane Central Register of Controlled Trials (CENTRAL; 2017, Issue 1). The CIS also searched trials registries for details of ongoing and unpublished studies. SELECTION CRITERIA: Randomised controlled trials (RCTs) comparing endovascular revascularisation (± conservative therapy consisting of supervised exercise or pharmacotherapy) versus no therapy (except advice to exercise) or versus conservative therapy (i.e. supervised exercise or pharmacotherapy) for IC. DATA COLLECTION AND ANALYSIS: Two review authors independently selected studies, extracted data, and assessed the methodological quality of studies. Given large variation in the intensity of treadmill protocols to assess walking distances and use of different instruments to assess QoL, we used standardised mean difference (SMD) as treatment effect for continuous outcome measures to allow standardisation of results and calculated the pooled SMD as treatment effect size in meta‐analyses. We interpreted pooled SMDs using rules of thumb (< 0.40 = small, 0.40 to 0.70 = moderate, > 0.70 = large effect) according to the Cochrane Handbook for Systematic Reviews of Interventions. We calculated the pooled treatment effect size for dichotomous outcome measures as odds ratio (OR). MAIN RESULTS: We identified ten RCTs (1087 participants) assessing the value of endovascular revascularisation in the management of IC. These RCTs compared endovascular revascularisation versus no specific treatment for IC or conservative therapy or a combination therapy of endovascular revascularisation plus conservative therapy versus conservative therapy alone. In the included studies, conservative treatment consisted of supervised exercise or pharmacotherapy with cilostazol 100 mg twice daily. The quality of the evidence ranged from low to high and was downgraded mainly owing to substantial heterogeneity and small sample size. Comparing endovascular revascularisation versus no specific treatment for IC (except advice to exercise) showed a moderate effect on maximum walking distance (MWD) (SMD 0.70, 95% confidence interval (CI) 0.31 to 1.08; 3 studies; 125 participants; moderate‐quality evidence) and a large effect on pain‐free walking distance (PFWD) (SMD 1.29, 95% CI 0.90 to 1.68; 3 studies; 125 participants; moderate‐quality evidence) in favour of endovascular revascularisation. Long‐term follow‐up in two studies (103 participants) showed no clear differences between groups for MWD (SMD 0.67, 95% CI ‐0.30 to 1.63; low‐quality evidence) and PFWD (SMD 0.69, 95% CI ‐0.45 to 1.82; low‐quality evidence). The number of secondary invasive interventions (OR 0.81, 95% CI 0.12 to 5.28; 2 studies; 118 participants; moderate‐quality evidence) was also not different between groups. One study reported no differences in disease‐specific QoL after two years. Data from five studies (n = 345) comparing endovascular revascularisation versus supervised exercise showed no clear differences between groups for MWD (SMD ‐0.42, 95% CI ‐0.87 to 0.04; moderate‐quality evidence) and PFWD (SMD ‐0.05, 95% CI ‐0.38 to 0.29; moderate‐quality evidence). Similarliy, long‐term follow‐up in three studies (184 participants) revealed no differences between groups for MWD (SMD ‐0.02, 95% CI ‐0.36 to 0.32; moderate‐quality evidence) and PFWD (SMD 0.11, 95% CI ‐0.26 to 0.48; moderate‐quality evidence). In addition, high‐quality evidence showed no difference between groups in the number of secondary invasive interventions (OR 1.40, 95% CI 0.70 to 2.80; 4 studies; 395 participants) and in disease‐specific QoL (SMD 0.18, 95% CI ‐0.04 to 0.41; 3 studies; 301 participants). Comparing endovascular revascularisation plus supervised exercise versus supervised exercise alone showed no clear differences between groups for MWD (SMD 0.26, 95% CI ‐0.13 to 0.64; 3 studies; 432 participants; moderate‐quality evidence) and PFWD (SMD 0.33, 95% CI ‐0.26 to 0.93; 2 studies; 305 participants; moderate‐quality evidence). Long‐term follow‐up in one study (106 participants) revealed a large effect on MWD (SMD 1.18, 95% CI 0.65 to 1.70; low‐quality evidence) in favour of the combination therapy. Reports indicate that disease‐specific QoL was comparable between groups (SMD 0.25, 95% CI ‐0.05 to 0.56; 2 studies; 330 participants; moderate‐quality evidence) and that the number of secondary invasive interventions (OR 0.27, 95% CI 0.13 to 0.55; 3 studies; 457 participants; high‐quality evidence) was lower following combination therapy.    Two studies comparing endovascular revascularisation plus pharmacotherapy (cilostazol) versus pharmacotherapy alone provided data showing a small effect on MWD (SMD 0.38, 95% CI 0.08 to 0.68; 186 participants; high‐quality evidence), a moderate effect on PFWD (SMD 0.63, 95% CI 0.33 to 0.94; 186 participants; high‐quality evidence), and a moderate effect on disease‐specific QoL (SMD 0.59, 95% CI 0.27 to 0.91; 170 participants; high‐quality evidence) in favour of combination therapy. Long‐term follow‐up in one study (47 participants) revealed a moderate effect on MWD (SMD 0.72, 95% CI 0.09 to 1.36; P = 0.02) in favour of combination therapy and no clear differences in PFWD between groups (SMD 0.54, 95% CI ‐0.08 to 1.17; P = 0.09). The number of secondary invasive interventions was comparable between groups (OR 1.83, 95% CI 0.49 to 6.83; 199 participants; high‐quality evidence). AUTHORS' CONCLUSIONS: In the management of patients with IC, endovascular revascularisation does not provide significant benefits compared with supervised exercise alone in terms of improvement in functional performance or QoL. Although the number of studies is small and clinical heterogeneity underlines the need for more homogenous and larger studies, evidence suggests that a synergetic effect may occur when endovascular revascularisation is combined with a conservative therapy of supervised exercise or pharmacotherapy with cilostazol: the combination therapy seems to result in greater improvements in functional performance and in QoL scores than are seen with conservative therapy alone.